Ranibizumab Pro Re nata versus Dexamethasone in the Management of Ischemic Retinal Vein Occlusion: Post-hoc Analysis from the COMRADE Trials. (3rd May 2020) - Pielen, Amelie; Feltgen, Nicolas; Hattenbach, Lars-Olof; Hoerauf, Hans; Bertelmann, Thomas; Quiering, Claudia; Vögeler, Jessica; Priglinger, Siegfried; Lang, Gabriele E.; Schmitz-Valckenberg, Steffen; Wolf, Armin; Rehak, Matus
ABSTRACT: Purpose : To compare ischemia-related clinical outcomes in patients treated with either ranibizumab pro re nata (PRN) or single dexamethasone implant in the Branch Retinal Vein Occlusion (COMRADE-B) or Central Retinal Vein Occlusion (COMRADE-C) trials. Methods : A post-hoc analysis of the Phase IIIb, 6-month, multicenter, double-masked, randomized, COMRADE-B and COMRADE-C trials. Change over 6 months in retinal ischemia status (central avascular [CA] zone and peripheral nonperfusion [PNP]), mean best-corrected visual acuity (BCVA), the development of shunt vessels and neovascularization, and frequency of laser therapy were assessed in retinal vein occlusion (RVO) patients treated with either ranibizumab 0.5 mg PRN or single dexamethasone 0.7 mg implant, as per European labels, in the COMRADE-B (N = 244; ranibizumab, 126, dexamethasone, 118) or COMRADE-C (N = 243; ranibizumab, 124, dexamethasone, 119) trials. BCVA progression in ischemic vs. non-ischemic patients based on the ischemia assessment at month 6 was carried out. Results : Visual acuity (VA) gains from baseline to month 6 were higher with ranibizumab than with dexamethasone in both patients with central ischemia and those with peripheral retinal nonperfusion, independent of the type of RVO (branch or central). The presence of CA and PNP had a significant impact on VA gain over 6 months in CRVO patients ( p < .0001), while there was no significant impact in BRVO. Ranibizumab was associated with less new ischemia than dexamethasone. Central RVO patients treated with dexamethasone received more laser treatments over the 6 months than those treated with ranibizumab, while there was no difference in the frequency of laser therapy between the branch RVO treatment groups. Conclusions : VA gain over six months in ranibizumab-treated RVO patients is not affected by ischemia, and is associated with less development of new ischemia during the first 6 months of treatment and equal or fewer laser treatments than dexamethasone implant.